Philosophy of Immunology - Pradeu, Thomas (Humanities, 2020)
In this Element, Thomas Pradeu considers the ways in which current immunology sheds light on some of the most important contemporary philosophical issues, from the persistence of identity through time to the interaction of mind and body. This title is also available as Open Access on Cambridge Core.